1997
DOI: 10.1046/j.1365-2249.1997.4121510.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for genetic heterogeneity in inflammatory bowel disease (IBD); HLA genes in the predisposition to suffer from ulcerative colitis (UC) and Crohn's disease (CD)

Abstract: SUMMARYFamily and epidemiological studies support a genetic susceptibility to UC and CD. Conflicting reports regarding associations between UC and HLA-DR2 and between CD and various HLA alleles have been published. The aim of this study was to determine whether molecularly defined HLA-DR genes are associated with these diseases in a Dutch group of patients. Fifty-nine unrelated Dutch UC patients and 89 CD patients were typed using DNA-based methods. A total of 2400 healthy local blood donors served as controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 30 publications
4
15
0
Order By: Relevance
“…Several previous studies have also observed associations of CD with DR13 in predominantly non-Jewish populations (1 6,25,28). Our association of CD with DR15 in the Jewish population has never previously been observed in CD patients although it has been observed in some studies of UC patients (15,24,27).…”
Section: Discussionsupporting
confidence: 56%
“…Several previous studies have also observed associations of CD with DR13 in predominantly non-Jewish populations (1 6,25,28). Our association of CD with DR15 in the Jewish population has never previously been observed in CD patients although it has been observed in some studies of UC patients (15,24,27).…”
Section: Discussionsupporting
confidence: 56%
“…Differences in the frequency of HLA haplotypes between males and females occur in inflammatory bowel disease: DR3-DQ2 frequency was reduced in females with UC 25 and DRB1*15 was increased only in female UC patients. 30 Two other regions that showed strong evidence for malespecific linkage were chromosomes 1q31-32 and 18p11 (Table 2 and Figure 1). Neither of these regions was identified by genome scans.…”
Section: 29mentioning
confidence: 99%
“…Ulcerative colitis (UC) is a chronic inflammatory mucosal disease associated with a strong familial pattern and a number of genetic loci implicated in disease susceptibility (5,29,36,37,49,53,54). Variation in penetrance, as well as demographic and epidemiologic features, indicates an important role for environmental factors in the inflammatory process of UC (38,48).…”
mentioning
confidence: 99%